2017
DOI: 10.1039/c7ra07272d
|View full text |Cite
|
Sign up to set email alerts
|

Composites of epoxy/graphene-modified-diamond filler show enhanced thermal conductivity and high electrical insulation

Abstract: In this work, we developed a single-step process to cast epoxy composites having a high thermal conductivity but a low electric conductivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The authors observed that the enhancement in SWCNT/epoxy samples rised much more rapidly than in CNF/epoxy composites (Figure ). Similar results can be found elsewhere …”
Section: Properties Of Epoxy Nanocompositessupporting
confidence: 91%
“…The authors observed that the enhancement in SWCNT/epoxy samples rised much more rapidly than in CNF/epoxy composites (Figure ). Similar results can be found elsewhere …”
Section: Properties Of Epoxy Nanocompositessupporting
confidence: 91%
“…Another significant class of GN/diamond materials is epoxy composites. Jiang et al Investigated the physical properties of such composites [165]. The materials exhibited high thermal and low electric conductivity.…”
Section: Materials' Processing Technologiesmentioning
confidence: 99%
“…Jiang et al, [11] developed Composites of epoxy/graphene modified diamond filler f thermal conductivity and high electrical insulation. Performance of the epoxy was improved by incorporating diamond microparticles that were covered with few-layer graphene sheets on surfaces it not only improved dispersion of diamond in the polymer matrix but it also decreased the interfacial thermal resistance between the diamond and Epoxy while preserving an excellent electrical insulation.…”
Section: Literature Reviewmentioning
confidence: 99%